2019
DOI: 10.1093/jas/skz017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of feed intake during late gestation on piglet birth weight and reproductive performance: a dose-response study performed in gilts

Abstract: The effects of increasing feed intake (1.8, 2.3, 2.8, and 3.3 kg/d) during late gestation of gilts on piglet birth weight and female reproductive performance were evaluated. A total of 977 gilts were fed a diet based on corn-soybean meal (3.29 Mcal ME per kg and 0.64% standardized ileal digestible lysine) from day 90 of gestation until farrowing. Gilts were weighed on days 90 and 112 of gestation, at farrowing and weaning. Born alive and stillborn piglets were weighed within 12 h of birth. Colostrum yield (CY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Colostrum intake and yield were similar, indicating that feed amount or timing did not impact colostrum production in the short period prior to farrowing. In contrast, Mallmann et al (2019) observed a decrease in colostrum yield when gilts were fed increasing amounts of gestation feed starting on day 90 of gestation. The authors concluded that the restricted fed gilts (1.8 kg/d) were mobilizing body protein and BF to meet demands for fetal growth and colostrum production prior to farrowing, with fat mobilization being prioritized for colostrum yield, therefore allowing for greater colostrum production in restricted-fed gilts.…”
Section: Discussionmentioning
confidence: 75%
“…Colostrum intake and yield were similar, indicating that feed amount or timing did not impact colostrum production in the short period prior to farrowing. In contrast, Mallmann et al (2019) observed a decrease in colostrum yield when gilts were fed increasing amounts of gestation feed starting on day 90 of gestation. The authors concluded that the restricted fed gilts (1.8 kg/d) were mobilizing body protein and BF to meet demands for fetal growth and colostrum production prior to farrowing, with fat mobilization being prioritized for colostrum yield, therefore allowing for greater colostrum production in restricted-fed gilts.…”
Section: Discussionmentioning
confidence: 75%
“…Feeding during the late gestation is critical to the development and growth of the fetuses and maternal tissues such as placenta, uterus, mammary tissue, retention of maternal lipid, and protein (Samuel et al, 2012;Mallmann et al, 2019). Therefore, proper nutrition is important for the litter birth weight, mammary development, milk production, and metabolic status of sows, which in turn may improve the piglet survivability, piglet weaning weight, and minimize body mobilization of sows (Mosnier et al, 2010;Theil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated reduced parturition time and stillbirths are associated with a higher energy status of the sow [34] and use of ber in sow diets [35]. However, stillbirths were not affected by increased feeding levels in late gestation [4], but gilts with lower feed intake had a lower percentage of stillbirths than gilts fed higher feed intake in late gestation [5]. Other factors such as litter size, birth weight, sow weight, parity, and assisted births can also impact stillbirths [12].…”
Section: Discussionmentioning
confidence: 91%
“…4 Percentage of sows having next parturition per sows having initial parturition. 5 Total born change is total born litter size of subsequent parturition minus total born litter size of previous parturition. Live born change is live born litter size of subsequent parturition minus live born litter size of previous parturition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation